Influence of Extrinsic and Intrinsic Motivation on Pupils Academic Performance in Mathematics - Adamma, Onyekwere Nonye; Ekwutosim, Okoro Pauline; Unamba, Eugene Chukwuemeka (SJME (Supremum Journal of Mathematics Education), 2018)
The study investigated the influence of extrinsic and intrinsic motivation on pupils’ academic performance in mathematics. Based on the purpose of the study two hypotheses guided the study. The descriptive research design was adopted for the study. The population of the study consisted of all 3056 primary six pupils in Owerri Education zone of Imo State.  A Sample size of 200 primary six pupils was selected for the study.   Simple random sampling technique was used in selecting four schools out of the nine schools. The instruments used for data collection was Academic Motivation Scale and Mathematics Achievement Test. The validity was determined by two experts in measurement and evaluation and one expert in mathematics education. The instruments have reliability coefficient of 0.89 and 0.92 determined using tests-retest method. Data generated were analyzed with the aid SPSS version.  Inferential statistics of t-test and Pearson product moment correlation were used to test the hypotheses at 0.05 level of significance. The study concludes that motivation improves academic performance of the pupils and there is a gender difference in motivation type and academic performance.